Instructional Design For The Teaching Of Arabic At Elementary Schools In Caraga Region Philippines - PANGANDAG, HAMDANIE ABEDIN; , Dr. Anam Sutopo, M.Hum; , Agus Wijayanto, Ph.D (2015)
Arabic language considered as one of the necessities and top priorities of a young Muslims to learn. This research seeks to discover and to explore the naturalistic study on Instructional Design for the teaching of Arabic at Elementary Schools in CARAGA Region, Philippines. More specifically, this research seeks to answer the following questions, namely: 1. what are the goals of instructions in teaching Arabic at Elementary Schools in CARAGA Region, Philippines?; 2. what are the instructional strategies used in teaching Arabic at Elementary Schools in CARAGA Region, Philippines?; 3. what are the instructional materials used in teaching Arabic at Elementary Schools in CARAGA Region, Philippines? and 4. how does teaching Arabic evaluated at Elementary Schools in CARAGA Region, Philippines? This study aimed to define the end goal of instruction in teaching Arabic; to find out the instructional strategies used in teaching Arabic; to determine the instructional materials used in teaching Arabic and to maximize the effectiveness, efficiency and appeal of instruction used in teaching Arabic at Elementary Schools in CARAGA Region, Philippines. Based on the obtained information, the data were analyzed. It was found that the Instructional end goal of teaching Arabic Language at Elementary School concerned with developing competence in the listening, speaking, reading and writing skills of the Muslim Learners. In addition, Asatidz in Arabic Language may use any teaching strategies as long as they are appropriate for the content of the lesson, and they accomplish the purposes set for the strategies. There is no specific order or unified law on Instructional Strategies in the Philippine Education prescribing or limiting the Asatidz to use in teaching Arabic Language. Moreover, the types of instructional materials used in teaching Arabic Language in Elementary School were teacher's designed instructional materials and commercial text book. The Madrasah Textbooks were donated by UNICEF and World Islamic Call Society (WICS), a Libyan-based International Organization. Finally, there are daily, monthly and yearly assessment and evaluation of teaching Arabic Language at Elementary School in CARAGA Region, Philippines. Keywords: Naturalistic Study, Instructional Design, and Teaching Arabic Language.